Dataset of Chinese language beginning learners reading speech and text-to-speech - Yoke Lian Lau (Figshare, 2023)
Three categories of audio recordings, a web service platform, and commercial software were involved in this analysis process. The three categories of audio recordings included eight filtered student recordings, an audio recording provided by a Mandarin instructor from University Malaysia Sabah, and an audio recording generated by Text-to-Speech MP3, available at https://ttsmp3.com/. All ten recordings will be uploaded into the NCH WavePad Sound Editor to build a spectrum image. This will allow us to compare and identify differences in tone reading, emotion reading, etc. You can download the NCH WavePad Sound Editor from https://www.nch.com.au/WavePad/index.html. This information is beneficial for all Mandarin language beginners and their teachers, as it can be used for comparison purposes. With this knowledge, they can further undertake a pilot study. This study provides a foundation for investigating differences in human and machine reading from multiple perspectives. Furthermore, this dataset can be used to analyze reading speed. It serves as a crucial starting point for spectrum, voice wave, and reader behavior research